2008
DOI: 10.4040/jkan.2008.38.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Wandering Behavior in Korean Elders with Dementia Residing in Nursing Homes

Abstract: Purpose: This study investigated various factors relatied to wandering behavior of Korean elders with dementia (KED). Methods: A sample of 160 ambulatory residents with dementia from 14 long term care facilities was used to examine demographic, individual, cognitive, physical health, and environmental characteristics by comparing wanderers (N=108) to nonwanders (N=52). Subjects were evaluated by Korean versions of the Mini-mental State Exam (K-MMSE), the Physical and Instrumental Activities of Daily Living (K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The present study estimated the rate of wandering as 30% in community-dwelling elders with dementia. Previous researches demonstrated 18.7% of drug-naïve community-dwelling Alzheimer's disease patients are wanderer,11 and 67.5% of nursing-home residing dementia patients are wanderer 14. These results are constant with a study that wandering behavior leads familial caregivers decide to place the patient in a nursing home or some other professional care facility 42…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The present study estimated the rate of wandering as 30% in community-dwelling elders with dementia. Previous researches demonstrated 18.7% of drug-naïve community-dwelling Alzheimer's disease patients are wanderer,11 and 67.5% of nursing-home residing dementia patients are wanderer 14. These results are constant with a study that wandering behavior leads familial caregivers decide to place the patient in a nursing home or some other professional care facility 42…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies estimated the rates of wandering as 17.4% in community dwelling patients with dementia, 10 18.7% in drug-naïve Alzheimer disease patients, 11 21% to 67.5% in nursing home residents. 12 13 14 Longitudinal studies indicate that wandering behavior starts on the average 10 months after diagnosis of dementia in 40% of individuals, 15 but eventually occurs in 80% of all patients with dementia. 16 In a large, multiethnic sample of community-dwelling patients, wandering was the most prevalent dementia-related behavior regardless of the ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary teams consisting of nurses, doctors, social workers, physiotherapists and psychologists have conducted various studies on the provision of cognitive interventions for people with dementia (Burgener et al, 2008; Hong & Kang, 2009; i Ferrer & Del Valle, 2014; Kang et al, 2010; Luttenberger et al, 2012; Tadaka & Kanagawa, 2007). Kang et al (2010) and Tadaka and Kanagawa (2007) presented clearly reported the roles, clinical experience and dementia‐related education of research assistants as intervention providers.…”
Section: Discussionmentioning
confidence: 99%
“…However, 85% of caregivers have indicated that wandering was one of the most significant factors influencing their experiences of burden (Kwon 1995, Kim & Jun 1996). A recent study has also reported that 67·5% of institutionalised PWDs displayed wandering behaviour (Song et al. 2008).…”
Section: Introductionmentioning
confidence: 98%